Ecological risk assessment of pesticides based on earthworms in soils on the southeast slopes of Mount Cameroon - Daniel Brice Kenko Nkontcheu; Agathe Lambou Fotio; Aimerance Donhachi Kenfack; Geraud Canis Tasse Taboue; Derick Atemlefac Acha; Eric Bertrand Fokam (Elsevier, 2023)
Agrochemicals misuse is common in developing countries with many environmental implications. This work assessed the ecological risk of pesticides, including insecticides, fungicides and herbicides based on earthworms in soils at the lower slopes of Mount Cameroon using the Pesticide Risk in the Tropics to Man, Environment and Trade (PRIMET) model. PRIMET was developed in 2008 in The Netherlands for use in tropical regions. Data on usage scheme and ecotoxicological information were collected and keyed into PRIMET for three main outputs: Predicted Environmental Concentration (PEC), No Effect Concentration (NEC), and Exposure Toxicity Ratio (ETR = PEC/NEC). Pesticides predicted for no acute and no chronic risk to earthworms included fipronil and chlorothalonil. Several pesticides were predicted for an acute risk to earthworms, and they comprised acetamiprid, imidacloprid, lambda-cyhalothrin, and carbendazim when used on maize (PEC ​= ​2.69 ​mg ​kg−1; ETR ​= ​5) and tomato (PEC ​= ​16.15 ​mg ​kg−1; ETR ​= ​30); 2, 4-D and abamectin when used on tomato and ethoprophos. Insecticides exhibiting a possible chronic risk to earthworms comprised acetamiprid, cypermethrin, emamectin benzoate, imidacloprid, indoxacarb, lambda-cyhalothrin, oxamyl, and thiametoxam. The majority of fungicides assessed (83%) posed a possible chronic terrestrial risk, with carbendazim at the top position when applied on tomato (PEC ​= ​16.15 ​mg ​kg−1; ETR ​= ​81). Some herbicides predicted for possible chronic risk based on earthworms included 2, 4-D, diuron, glyphosate, ethoprophos, and metaldehyde. Pesticides with the highest risk to earthworms comprised chlorpyrifos-ethyl, imidacloprid, ethoprophos, and nicosulfuron. The riskiest pesticides should hereby be regulated or replaced by less risky ones. The measurement of pesticide residues in water and food in the various agroecological zones of Cameroon is necessary to shed more light on pesticide ecotoxicology.